2022
DOI: 10.1124/dmd.121.000707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications and the Roles of Transporters in Disposition, Tumor Targeting, and Tissue Toxicity of meta-Iodobenzylguanidine

Abstract: Transporters on the plasma membrane of tumor cells are promising molecular "Trojan horses" to deliver drugs and imaging agents into cancer cells. Radioiodine-labeled metaiodobenzylguanidine (mIBG) is used as a diagnostic agent ( 123 I-mIBG) and a targeted radiotherapy ( 131 I-mIBG) for neuroendocrine cancers. mIBG enters cancer cells through the norepinephrine transporter (NET) where the radioactive decay of 131 I causes DNA damage, cell death, and tumor necrosis. mIBG is predominantly eliminated unchanged by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…17 Moreover, other transporters play a role in renal excretion of MIBG, including human organic cation transporter 2 (hOCT2) and multidrug and toxin extrusion proteins 1 and 2-K (hMATE1/2-K). 17 A better understanding of these mediators of 131 I-MIBG efflux and clearance may lead to an improved prediction of clinical outcomes. Finally, while it is tempting to try to link NET and VMAT2 protein expression mechanistically with response to 131 I-MIBG therapy, it is important to note that our findings represent statistical associations and cannot speak to the mechanism of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Moreover, other transporters play a role in renal excretion of MIBG, including human organic cation transporter 2 (hOCT2) and multidrug and toxin extrusion proteins 1 and 2-K (hMATE1/2-K). 17 A better understanding of these mediators of 131 I-MIBG efflux and clearance may lead to an improved prediction of clinical outcomes. Finally, while it is tempting to try to link NET and VMAT2 protein expression mechanistically with response to 131 I-MIBG therapy, it is important to note that our findings represent statistical associations and cannot speak to the mechanism of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that there are likely several other important contributing factors mediating radiation responsiveness as well as 131 I‐MIBG uptake, retention, and efflux. For example, the role of multidrug resistance protein 1 and 4 (MRP1/4; ABCC1/4) in efflux has recently been reported 17 . Moreover, other transporters play a role in renal excretion of MIBG, including human organic cation transporter 2 (hOCT2) and multidrug and toxin extrusion proteins 1 and 2‐K (hMATE1/2‐K) 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, OCT3 has been identified as the primary transporter facilitating mIBG into the heart and salivary glands [ 44 ]. We and others have thus proposed that inhibition of OCT3 could be a viable clinical strategy to improve the safety and tumor selectivity of mIBG in cancer patients [ 25 , 45 , 46 ]. Here, we showed that brigatinib exhibits potent and preferential in vitro inhibition of hOCT3 ( Figure 2 and Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitously expressed hOCT3 has not only been implicated in the transport of anti-cancer drugs, but also as a biomarker for cancer pathogenesis [39]. For example, in colorectal cancers hOCT together with its paralogues, hOCT1 and hOCT2, have been shown to be determinants of oxaliplatin cytotoxicity [8,[39][40][41]. Moreover, SLC22A3 expression in renal cell carcinoma cell lines enhances the sensitivity of these cell lines towards the chemotherapeutic agents melphalan, irinotecan, and vincristine [9].…”
Section: Multiplex Pcrmentioning
confidence: 99%